On Solutions of Some Polynomial-Functional Equations. - Bekbaev, U. D. (Universiti Putra Malaysia Press, 2002)
Systems of some polynomial-functional equations, which are derived from the usual properties of derivative, are considered. Solutions of these systems over a field and their canonical forms relative to natural equivalences are given.